Modern requirements for noise immunity aircraft navigation equipment - Zavalishin, Oleg Ivanovich; Zatuchny, Dmitry Alexandrovich; Shatrakov, Yury Grigorievich (Springer Aerospace Technology (SAT), 2021)
This book presents a technical solution to ensuring the noise immunity of navigation systems in civil aviation aircrafts at the stages of their terminal procedures. It highlights instrumental precision approaches to landing and landing in automatic mode using satellite and inertial radio navigation systems and ground-based augmentation used as the primary means, in accordance with the ICAO requirements. The book is intended for engineering and technical specialists engaged in the development, manufacture and operation of on-board radio electronic systems of aircrafts and ground-based radio engineering support for flights, as well as graduate students and senior students of radio engineering specialties. It is also useful for professionals whose activities are related to air traffic control.